# How do you balance this redox reaction using the oxidation number method? HNO3(aq) + H3AsO3(aq) --> NO(g) + H3AsO4(aq) + H2O(l)

##### 1 Answer

You follow a series of steps in order.

Here are the steps for balancing redox equations.

Your unbalanced equation is

HNO₃ + H₃AsO₃ → NO + H₃AsO₄ + H₂O

**Step 1.** The oxidation numbers are:

Left hand side: H= +1; N= +5; O = -2; As = +3

Right hand side: N = +2; O = -2; H = +1; As = +5

**Step 2.** The changes in oxidation number are:

N: +5 → +2; Change = -3

As: +3 → +5; Change = +2

**Step 3.** You need 3 atoms of As for every 2 atom of N.

This gives you total changes of +6 and -6.

**Step 4.** Insert coefficients to get these numbers.

**2** HNO₃ + **3** H₃AsO₃ → **2** NO + **3** H₃AsO₄ + H₂O

**Step 5.** Balance O.

**2** HNO₃ + **3** H₃AsO₃ → **2** NO + **3** H₃AsO₄ + **1** H₂O

**Step 6.** Balance H.

Done.

**Step 7.** Check that all atoms balance.

Left hand side: 11 H; 2 N; 15 O; 3 As

Right hand side: 2 N; 15 O; 11 H; 3 As

The balanced equation is

2HNO₃ + 3H₃AsO₃ → 2NO + 3H₃AsO₄ + H₂O